THE ROLE OF PANCASILA EDUCATION IN SHAPING STUDENT CHARACTER IN THE DIGITAL AGE - Nining Suryaningsih. Y (INJOSEDU: International Journal of Social and Education, 2025)
The digital era has brought significant changes in the mindset, behaviour, and social interactions of students. In this context, Pancasila education has a strategic role as an instrument for character building based on national values, morality, and social responsibility. This study aims to analyse the role of Pancasila education in shaping student character in the digital era, which is characterised by a massive flow of information and the influence of globalised values. The research method used is a qualitative descriptive approach with data collection techniques through literature study and observation of the implementation of Pancasila education in higher education. The results show that Pancasila education plays an important role in instilling the values of integrity, mutual cooperation, tolerance, and nationalism in students. These values form the foundation for shaping an ethical, critical, and community-oriented digital character. However, the main challenges faced are the low interest of students in Pancasila courses and the dominance of digital media, which often contradicts Pancasila values. Therefore, innovation is needed in interactive and contextual technology-based learning methods so that Pancasila education remains relevant in shaping student character in the digital era.